Pengaruh Jumlah Penduduk, Tingkat Pengangguran Terbuka, dan Pendidikan Terhadap Kemiskinan di Indonesia - Muhammad Hafiz Fadhilah; Masruri Muchtar; Pardomuan Robinson Sihombing (Jurnal Manajemen Publik dan Kebijakan Publik (JMPKP), 2023)
This study aims to determine the effect of population size, unemployment rate, education, and the Gini ratio on poverty in Indonesia. The research was conducted using panel data regression with a random effect regression model. The results of the study show that population, unemployment rate, education and the gini ratio simultaneously affect the number of poor people in Indonesia. Partially, all independent variables affect the number of poor people but with a different direction of influence.